Risk assessment and spatial distribution characteristics of heavy metals in soil of typical vegetable planting areas in Wuqing - SU Huiyue (Agro-Environmental Protection Institute, Ministry of Agriculture, 2021)
Heavy metal pollution has seriously endangered human health and food security. In order to explore the dynamic changes of heavy metals in soil in different periods, a total of 95 surface soil samples(bulk soil) were collected from Wuqing District, Tianjin, China. Then the heavy metals(i.e., As, Cd, Cu, Cr, Ni, Pb, and Zn) concentrations in these simples were quantified. The spatial distribution of soil heavy metals in farmland was analyzed based on geostatistical analysis to explore the accumulation of heavy metals in soil, potential ecological risks and sources of heavy metals in soil. The results showed that the cumulative pollution of heavy metals Pb, Cu, Cr, Zn, Cd and As increased with time except Ni. The geoaccumulation index and potential ecological risk index indicated that Cd and As in the study area were the main contributors to the total ecological risk. The spatial characteristics of heavy metals in 2005 and 2019 showed that Cu, Cr, Ni, Zn and As had similar spatial distribution, the high-value areas were concentrated in the southwest of the study area. The highvalue areas of Pb showed non-point source pollution, while Cd showed obvious point source pollution. Cu was mainly affected by agricultural fertilization, Zn was mainly affected by agricultural fertilization and sewage irrigation. As, Ni and Cr was mainly caused by soil parent material. Cd might originate from industrial activities. Pb was attributed to traffic exhaust emissions. The study have shown that the main causes of heavy metal accumulation were industrial emissions and sewage irrigation. This study clarifies the spatial distribution characteristics and pollution sources of heavy metals in soil in Wuqing District, Tianjin, which can provide theoretical basis for pollution control and ecological protection in the study area.